A systematic review and narrative synthesis of health literacy interventions among Spanish speaking populations in the United States - Joel Hernandez; Liliana Demiranda; Priyanka Perisetla; Lauren Andrews; Keer Zhang; Rebecca Henderson; Ajay Mittal; Hannah F. Norton; Melanie G. Hagen (BMC, 2024)
Abstract Background While many populations struggle with health literacy, those who speak Spanish preferentially or exclusively, including Hispanic, immigrant, or migrant populations, may face particular barriers, as they navigate a predominantly English-language healthcare system. This population also faces greater morbidity and mortality from treatable chronic diseases, such as hypertension and diabetes. The aim of this systematic review was to describe existing health literacy interventions for patients with a Spanish-language preference and present their effectiveness. Methods We carried out a systematic review where Web of Science, EMBASE, and PubMed were queried using MeSH terms to identify relevant literature. Included articles described patients with a Spanish-language preference participating in interventions to improve health literacy levels in the United States. Screening and data abstraction were conducted independently and in pairs. Risk of bias assessments were conducted using validated appraisal tools. Results A total of 2823 studies were identified, of which 62 met our eligibility criteria. The studies took place in a variety of community and clinical settings and used varied tools for measuring health literacy. Of the interventions, 28 consisted of in-person education and 27 implemented multimedia education, with 89% of studies in each category finding significant results. The remaining seven studies featured multimodal interventions, all of which achieved significant results. Conclusion Successful strategies included the addition of liaison roles, such as promotores (Hispanic community health workers), and the use of multimedia fotonovelas (photo comics) with linguistic and cultural adaptations. In some cases, the external validity of the results was limited. Improving low health literacy in patients with a Spanish-language preference, a population with existing barriers to high quality of care, may help them better navigate health infrastructure and make informed decisions regarding their health. Registration PROSPERO (available at https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021257655.t ).